Study on the factors of delay in construction works - Carvalho, André Brasil (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2021)
The delay in civil construction works is observed globally and affects the economy of countries. Therefore, identifying the causes of delays is of paramount importance to minimize their consequences. This paper aims at identifying the causes of delay in construction works and their analysis and existing correlations through statistical factor analysis. The research methodology included a Systematic Literature Review (SLR), a Survey Research through questionnaires and interviews was conducted, as well as the identification of the main causes of delay through the Relative Importance Index (RIL) and the ABC Curve. Finally, factor analysis of the causes of delay was performed, not limiting only to their identification. The results showed that the 12 identified causes are correlated to 4 delay factors, which account for 69.18% of the sample variance: supply management (21.41%); workforce management (20,79%); project management (17.64%) and management of climatic conditions (9.34%). It is concluded hereby that the delay factors mentioned herein can be considered management deficiencies in the projects and that the research has expanded the knowledge on construction delays, thus contributing to the frontier of knowledge to mitigate this problem in several countries, especially developing ones.